Evolutionary Ethics’ Tradition within Contemporary Context - Kalenda, Česlovas (Problemos, 2007)
The article discusses the role performed by evolutionary ethics in the specification of causes of the emergence of present-day ecology problem and in the determination of methodological foundations for relevant solutions. The formulation of such particular goal was prompted by the universally inadequate human responses to the unfavourable ecological condition on the planet indicating the obvious underdevelopment of moral abilities compared to the development of technological changes. The article seeks to treat this problem from the point if view of evolutionary ethics focusing on the circumstances and the character of the formation of cognitive and moral qualities in a human determined, possibly, not only by the characteristics of his historical and cultural development. Drawing on the history of philosophy (D. Hume, A. Smith, H. Spencer, P. Kropotkin) and research findings (Ch. Darwin, E.O. Wilson), the sources, the development, and the current contents of evolutionary ethics is revealed (H. Mohr). Having started from the premise that ethics must have emerged from social instincts inherent in human nature, the evolutionary ethics has reached the point of a sociobiological project seeking to base the objective quality of ethical value of human behaviour on the genetic arguments. Criticising the extremely challenging ideas, the present article gives a positive evaluation to the attempts to explain the development of moral abilities demonstrated by Homo sapiens sapiens by biological or culturally-interacting factor models. This particular methodological approach, as is indicated by the findings of Roman Club members, enables a more profound and clear understanding of the causes of current ecological crisis, and to give a more precise definition and prognosis of the ways and tempo of its fighting.